Modelo de producción asociativa para la asociación APIVIDA del cantón Chone - Sánchez Bravo, Richard Eduardo (2020)
The objective of this research was to develop an associative production model for the Apivida association of Chone canton. A diagnosis was made of the current form of production that the association applies, in order to know the restrictions that prevent satisfying the demand for honey. For the development of the research, a methodology was used with a mixed approach, non-experimental, bibliographic and field, with descriptive and exploratory scope. Surveys were developed and the president of the association was interviewed to know his opinions about the topic and the current situation of the organization. In a bibliographic way, the associations, their types and their behavior in Ecuador were examined. Proposals for associativity models that are presented in business practice were studied in order to identify those that correspond to the particularities of the association under study and that are in accordance with the Ecuadorian legal system. Aspects related to competitiveness were analyzed, the elements that are part of the associativity model were defined and a model proposal was applied to validate it in the Apivida association of Chone canton. As a result of the diagnosis made it was found that honey producers do not have an associative culture and this makes their behavior in the processes of production and marketing. A proposal for a model of associativity to be implemented was determined in order to contribute to a consolidated and competitive association.